Assessing the Effectiveness of Adding Various Plant Extracts in Extending the Shelf- Life of Soft Cheese - Muhsin, Muhsin Falih AL-Quraishi (University of Thi-Qar Journal of agricultural research, 2024)
The study aimed to prepare various plant extracts and estimate their effectiveness in improving certain chemical properties and prolonging the shelf life of soft cheese during a storage period of 14 days at a temperature ranging from 5-7°C. Three treatments (T1, T2, T3) were implemented by adding 5% volume/volume of oil extracts (fenugreek, cinnamon, black seed) respectively to the milk used in the enzymatic preparation of soft cheese, in addition to the control treatment (without addition). The results showed the effectiveness of adding oil extracts in supporting the quality of soft cheese stored under refrigeration, which contributed to reducing the logarithmic growth in the number of bacteria types. The control treatment samples recorded a significant increase in the total number of bacteria (total bacteria, coliform bacteria, lactic acid bacteria, psychrophilic bacteria, and fungi) compared to the samples from T1, T2, and T3 during the storage period. The T3 treatment samples obtained the best results, as they recorded the lowest increase in the total number of bacterial types under study. Additionally, the results indicated the role of plant extracts in maintaining the quality characteristics of soft cheese during the storage period. The control treatment samples exhibited the lowest results compared to the other treatments, recording a significant decrease in the percentage of moisture, which reached 60.07%, while the T1 sample achieved the best results with a moisture content of 61.43%. The control sample also showed a significant increase in the percentage of total acidity, which reached 0.91%, while the T3 sample recorded an acidity percentage of 0.51%. There were no notable differences in the protein percentage at the end of all treatments.